Effects of postharvest methyl jasmonate treatment on aromatic volatile biosynthesis by 'Nanguoli' fruit at different harvest maturity stages. Issue 3 (3rd July 2017) - Qin, G. H.; Wei, S. W.; Tao, S. T.; Zhang, H. P.; Huang, W. J.; Yao, G. F.; Sha, S. F.; Zhang, S. L.
ABSTRACT: The ripe fruit of Pyrus ussuriensis 'Nanguoli' is favoured by people for its attractive colour, exquisite flesh and pleasant flavour. However, its flavour is negatively affected by early harvest. Therefore, this study aimed to determine whether exogenous methyl jasmonate (MJ) can help to regulate aromatic volatiles biosynthesis in pre-climacteric 'Nanguoli' fruit at different maturity stages (135 days after full bloom (DAFB) or 'early harvested' and 145 DAFB or 'normal harvested'). MJ promoted aromatic volatile biosynthesis in normal harvested fruit, with the number of volatile compounds increasing from 43 in untreated fruit to 51 and 57 in fruit that had been treated with 1 and 5 mM MJ, respectively. By contrast, MJ had little effect on early harvested fruit, which exhibited an increase from 41 to 49 and 44 volatile compounds following treatment with 1 and 5 mM MJ, respectively. The total content of aromatic volatiles also increased by 53.75% and 66.82% in normal harvested fruit treated with 1 and 5 mM MJ, respectively, whereas early harvested fruit exhibited only slight increases. There was no significant difference between the effects of 1 and 5 mM MJ on aromatic volatile biosynthesis, indicating that the observed effects were dependent on the maturity stage of the fruit rather than the exogenous MJ concentration within the range tested. The ethylene production rate exhibited similar changes to those observed for the aromatic volatile content and there were no significant differences in the aromatic volatile contents of 'Nanguoli' fruits that had been treated with 1-methylcyclopropene (1-MCP) + MJ at different maturity stages. Therefore, it is deduced that ethylene may trigger aromatic volatile biosynthesis.